50th Anniversary Article: Organizational Behavior, Strategy, Performance, and Design in Management Science - Boudreau, John W. (Management Science, 2004)
This article provides a personal perspective on the themes and topics that have emerged in research published by the department of organizational behavior, in the first 50 years of Management Science. A review of articles accepted by the department suggests several themes that reflect broad objectives, such as “improving management science models,” or distinguishing points of view or assumptions, such as “treating organizations as decision-making entities.” The research is summarized through topics and subtopics that classify the subjects and findings of the research, identifying the relative popularity of the topics, and their contribution to each of the themes. The pattern suggests that as a “behavioral” department in a journal characterized by managerial practice, optimization, and the context of real work organizations, research is uniquely grounded in applications, solutions, and work consequences in ways that are less prevalent in typical outlets for behavioral research. The article concludes by suggesting that there are ample signs of convergence across departments in the journal. Scholars in organizational behavior increasingly recognize that the context provided by other management disciplines provides essential insights. Likewise, scholars in other management disciplines increasingly recognize the value of integrating behavioral theories and findings into their frameworks and models.